(untitled) (Web of Teachers: Inderscience Research, 2026)
In the modern era of globalization, English has become the leading language in communication, science, technology, trade, and culture. Consequently, the effective teaching of English, utilizing innovative methodologies and up-to-date educational technologies, is of paramount importance across the globe. The success of English language teaching depends on the comprehensive integration of modern approaches and tools, taking into account the needs of learners, the context of teaching, and the rapid development of information and communication technologies. The teaching and learning of English are a dynamic process that continuously adapts to new challenges, opportunities, and the ever-changing demands of the world.